Influence of court surfaces on impact cushioning during basketball lay-up - Quek, Raymond Kai Kiat (2014)
Indoor and outdoor playing surfaces with different cushioning properties can affect movement impact. However, no study has compared impact loading between wooden and asphalt basketball courts. This study compared plantar pressure parameters for the four steps of the lay-up on the wooden and asphalt courts. Thirteen healthy males were evaluated in the randomized crossover study wearing the Novel Pedar-X system. Peak contact force, peak pressure and pressure-time integral were measured in eight regions: hallux, lesser toes, medial, central and lateral forefoot, medial and lateral arch and the heel. The contact area was analysed as a whole step. Wilcoxon signed-rank test was used for statistical analysis. Higher peak forces were observed on the wooden surface at the hallux (p=0.033) [wooden: 70.63(32.37) N, asphalt: 61.38(30.81) N] and medial forefoot (p=0.013) [wooden: 146.39(48.89) N, asphalt: 123.46(49.17) N] of the right landing step. Peak force measured for the left landing step was higher at the lesser toes (p=0.009) [wooden: 162.30(60.09) N, asphalt: 148.33(56.78) N] but lower at the lateral forefoot (p=0.039) [wooden: 163.58(53.79) N, asphalt: 179.45(63.98) N] and lateral arch (p=0.039) [wooden: 144.47(74.95) N, asphalt: 172.90(58.99) with smaller contact area (p=0.033) [wooden: 121.35(16.92) cm2, asphalt: 126.95(14.44) cm2]. No differences for peak pressure and pressure-time integral were found. Results suggest that the wooden surface may elicit a better landing technique by increasing bending at the ankles and decreasing inversion to disperse contact forces more effectively. Additionally, perceived impact of the surface may affect landing strategy. More investigation is needed due to complications in sport-specific movement.